Causal associations of fatigue and functional outcome after ischemic stroke: a mediation Mendelian randomization study - Jiang, Ping; Gao, Ying; Zhang, Leyi; Jiang, Li; Li, Chuanpeng (Frontiers in Neurology, 2024)
Background and objectives Fatigue has been associated with adverse effects on recovery from ischemic stroke based on previous observational research. The purpose of our study was to explore the potential causal association of fatigue with poor functional outcome after ischemic stroke by employing Mendelian randomization (MR). Methods A set of instrumental variables, comprising 36 single-nucleotide polymorphisms (SNPs) that are only related to fatigue, were derived from a genome-wide association study (GWAS) that included 449,019 general individuals. The functional outcomes after ischemic stroke were derived from a GWAS (Genetics of Ischemic Stroke Functional Outcome Network) involving 6,021 survivors. Two-sample MR methods were used to assess the causal effect, including inverse variance weighted, MR-Egger, weighted median, simple mode, and weighted mode. In bidirectional MR analysis, the reverse causal association was analyzed using the Wald ratio method. The mediation effects of lipid metabolites were analyzed using two-step MR analysis. Results Genetic liability to fatigue was causally associated with the poor functional outcome (modified Rankin Scale ≥3 at 3 months) after ischemic stroke (OR = 4.20, 95%CI [1.11–15.99], p < 0.05). However, genetic predicted poor functional outcome after ischemic stroke was not associated with fatigue (OR = 1.00, 95%CI [0.99–1.02], p > 0.05). The results of the two-step MR showed that cholesteryl esters to total lipids ratio in large very low-density lipoprotein (VLDL) (ME = −0.13, p < 0.05); concentration of very large VLDL particles (ME = −0.13, p < 0.05); free cholesterol in large VLDL (ME = −0.13, p < 0.05); free cholesterol to total lipids ratio in very large VLDL (ME = −0.22, p < 0.05); phospholipids in large VLDL (ME = −0.15, p < 0.05); phospholipids in very large VLDL (ME = −0.13, p < 0.05); phospholipids to total lipids ratio in large high-density lipoprotein (HDL) (ME = −0.17, p < 0.05); total lipids in very large VLDL (ME = −0.14, p < 0.05); triglycerides in small VLDL (ME = −0.11, p < 0.05); and triglycerides to total lipids ratio in large HDL (ME = −0.10, p < 0.05) assumed a pivotal role in mediating the association between fatigue and poor functional outcome after ischemic stroke. Conclusion Our study provides evidence supporting the causal association between fatigue and the poor functional outcome after ischemic stroke, which emphasizes the importance of implementing interventions aimed at addressing fatigue. This could offer a therapeutic target to improve recovery after ischemic stroke and warrant exploration in a clinical context. One potential mechanism by which fatigue affects functional outcomes after ischemic stroke is through the action of lipid metabolites.